Electrostatic-magnetic-hybrid thrust generation in central–cathode electrostatic thruster (CC–EST). (November 2018) - Sasoh, Akihiro; Kasuga, Hayato; Nakagawa, Yoshiya; Matsuba, Toshihiro; Ichihara, Daisuke; Iwakawa, Akira
Abstract: The thrust characteristics of electrostatic-magnetic hybrid acceleration have been obtained in the central–cathode electrostatic thruster (CC-EST), which has a diverging magnetic nozzle and injects propellant through an annular slit on the inner surface of a ring anode. The electrostatic and electromagnetic contributions are evaluated by fitting experimentally measured thrust characteristics to formulae derived for steady-state, quasi-neutral plasma flows. The thrust is composed of two terms: one corresponds to the electrostatic acceleration interfaced by the magnetized electrons, the other to electromagnetic acceleration yielding a kinetic energy of swirl motion that is converted to that of axial motion in the diverging magnetic nozzle. The thrust performances of three thrusters having an axisymmetric shape with a hollow cathode on the centre axis and a diverging, applied magnetic field are examined. While only an electromagnetic thrust component is obtained in the conventional applied-field magneto-plasma-dynamics thruster, the other two, CC–ESTs, exhibit comparable, electrostatic and electromagnetic thrust components, and thus improve thrust performance. Highlights: A central–cathode electrostatic thruster (CC-EST) is developed. Electrostatic-magnetic hybrid thrust is obtained in CC-EST. The thrust components are formulated based on magnetoplasmadynamics. The electrostatic and electromagnetic thrusts are found competitive. CC-EST has a potential to have both high thrust density and high thrust efficiency.